2003
DOI: 10.1124/jpet.103.051912
|View full text |Cite
|
Sign up to set email alerts
|

The Subtype-Selective Nicotinic Acetylcholine Receptor Agonist SIB-1553A Improves Both Attention and Memory Components of a Spatial Working Memory Task in Chronic Low Dose 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine-Treated Monkeys

Abstract: Monkeys that receive chronic low dose (CLD) 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) administration develop deficits in spatial delayed-response task performance. The present study examined the extent to which SIB-1553A [(Ϯ)-4-{[2-(1-methyl-2-pyrrolidinyl)ethyl]thio}phenol hydrochloride], a novel neuronal nicotinic acetylcholine receptor (nAChR) agonist with selectivity for ␤4 subunit-containing nAChRs, could counteract this cognitive deficit produced by CLD MPTP exposure. Prior to MPTP treatment, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 28 publications
5
32
0
Order By: Relevance
“…It has been postulated that cognitive dysfunction in PD may actually precede the onset of motor symptoms (Schneider and Pope-Coleman 1995). Accordingly, low dose MPTP administration in monkeys has been used to model this presymptomatic parkinsonian state and produces persistent cognitive deficits in the face of transient or absent motor signs (Taylor et al 1990;Schneider and Roeltgen 1993;Schneider et al 1994aSchneider et al , 1994bSchneider et al , 1999Schneider et al , 2003FernandezRuiz et al 1995FernandezRuiz et al , 1999Schneider and Pope-Coleman 1995), including deficits in spatial delayed response and object retrieval. While the extent to which the deficits in spatial working memory reflect prefrontal versus striatal dopamine loss is not yet known, elevating dopaminergic stimulation can restore cognitive function in this model (see below).…”
Section: Primate Models Of Dopamine Dysfunction and Cognitive Impairmentmentioning
confidence: 98%
“…It has been postulated that cognitive dysfunction in PD may actually precede the onset of motor symptoms (Schneider and Pope-Coleman 1995). Accordingly, low dose MPTP administration in monkeys has been used to model this presymptomatic parkinsonian state and produces persistent cognitive deficits in the face of transient or absent motor signs (Taylor et al 1990;Schneider and Roeltgen 1993;Schneider et al 1994aSchneider et al , 1994bSchneider et al , 1999Schneider et al , 2003FernandezRuiz et al 1995FernandezRuiz et al , 1999Schneider and Pope-Coleman 1995), including deficits in spatial delayed response and object retrieval. While the extent to which the deficits in spatial working memory reflect prefrontal versus striatal dopamine loss is not yet known, elevating dopaminergic stimulation can restore cognitive function in this model (see below).…”
Section: Primate Models Of Dopamine Dysfunction and Cognitive Impairmentmentioning
confidence: 98%
“…Although L-DOPA is unable to ameliorate the VDR performance (Schneider et al 2012), nAChR agonists SIB-1508Y and SIB-1553A induced a long-lasting improvement in performance (Schneider et al 1999(Schneider et al , 2003. Coherent with this data, postmortem studies performed on MPTP-treated animals have shown that whereas cortical dopaminergic levels are intact, norepinephrine levels are reduced in both the cortex and the caudate nuclei.…”
Section: Mptp-based Nonhuman Primate Modelmentioning
confidence: 98%
“…Control subjects perform the task with a delay-dependent increase in errors, up to a chance level, reflecting the limits of their short-term spatial memory. In contrast, MPTP-treated monkeys poorly perform in this test, shifting from a delay-dependent to a delay-independent performance profile, producing the same kind of errors as the control subjects, regardless of the delay length (Schneider et al 1999).Although L-DOPA is unable to ameliorate the VDR performance (Schneider et al 2012), nAChR agonists SIB-1508Y and SIB-1553A induced a long-lasting improvement in performance (Schneider et al 1999(Schneider et al , 2003. Coherent with this data, postmortem studies performed on MPTP-treated animals have shown that whereas cortical dopaminergic levels are intact, norepinephrine levels are reduced in both the cortex and the caudate nuclei.…”
mentioning
confidence: 99%
“…Monkeys that have previously received a chronic low dose of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) may develop attentional deficits, and it has been reported that SIB-1553A, a novel agonist with selectivity for β4-containing nAChRs, may counteract this type of cognitive deficit (Schneider et al 2003). It is of particular interest that at lower doses, SIB-1553A appeared more effective in improving attentional deficits in monkeys associated with chronic MPTP exposure, whereas at higher doses, SIB-1553A appeared to effectively improve both attentional and memory performances (Schneider et al 2003).…”
Section: Nicotinic Receptor Subtypes Underlying Nicotinic Modulation mentioning
confidence: 99%